Effects of protein level, calcium:phosphorous ratio and monensin on performance of finishing steers - S. Durham; Jack G. Riley; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1981)
Ration crude protein levels of 10.4% and 12.0% were fed with or without monensin and with calcium-to-phosphorous ratios (Ca:P) of 1:2, 2:1, or 1:1. Steers fed 10.4% crude protein, a 1:1 Ca:P, and Monensin had highest average daily gains and were most efficient. Extra protein in the 12% ration or the extra calcium in the 2:1 ration produced no benefits. Phosphorous in the 1:2 Ca:P apparently was excessive, as indicated by depressed daily gain and poorer efficiency. Monensin significantly increased average daily gain and improved feed efficiency.
Keywords: Cattlemen& #x27; s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Protein; Calcium:phosphorous ratio; Monensin; Performance; Steers